Social dimensions of disaster resilience - Marchezini, Victor (2019)
There are few disaster studies conducted by social scientists in Brazil, in particular research related to the disaster recovery process. The debate about disaster recovery has been led by the natural and hard sciences, which have used it to frame disaster as an event that requires coping mechanisms and resilience strategies in order to bounce back. The term ‘resilience’ emerged in the biological and hard sciences and has been applied to human societies. Although the participation of social scientists in this debate is increasing, it is still rare to encounter sociological studies about resilience to disasters. The aim of this article is to discuss the concept of disaster resilience in light of the sociology of disaster. Based on bibliographic reviews, desk research and field research activities in the affected towns of Ilhota/Santa Catarina State (2008) and São Luiz do Paraitinga/São Paulo State (2010), the research discusses theoretical and methodological pathways to comprehend the social dimensions of disaster resilience.